2012
DOI: 10.1111/j.1467-9450.2012.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition bias and the physical attractiveness stereotype

Abstract: Previous studies have found a recognition bias for information consistent with the physical attractiveness stereotype (PAS), in which participants believe that they remember that attractive individuals have positive qualities and that unattractive individuals have negative qualities, regardless of what information actually occurred. The purpose of this research was to examine whether recognition bias for PAS congruent information is replicable and invariant across a variety of conditions (i.e. generalizable). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Facial attractiveness can be detected in a glance or in a task unrelated to the explicit task of judging facial attractiveness, thus suggesting the automatic processing of facial attractiveness. [25][26][27][28][29] Given the variation in the reported findings on how facial attractiveness stereotype is processed, testing whether facial attractiveness is a predictive factor of good personality traits in a priming task is interesting. Previous studies have found a recognition bias for information consistent with the physical attractiveness stereotype.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Facial attractiveness can be detected in a glance or in a task unrelated to the explicit task of judging facial attractiveness, thus suggesting the automatic processing of facial attractiveness. [25][26][27][28][29] Given the variation in the reported findings on how facial attractiveness stereotype is processed, testing whether facial attractiveness is a predictive factor of good personality traits in a priming task is interesting. Previous studies have found a recognition bias for information consistent with the physical attractiveness stereotype.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have found a recognition bias for information consistent with the physical attractiveness stereotype. 29 In this study, positive personality words primed by attractive faces or negative personality words primed by 30 unattractive faces are defined as congruent trials, whereas positive personality words primed by unattractive faces or negative personality words primed by attractive faces are defined as incongruent trials. If beauty is good, in the congruent conditions, the emotional valence of the attractive faces should be consistent with the valence of the positive personality words, and similarly for the unattractive faces and negative personality words.…”
Section: Introductionmentioning
confidence: 99%
“…This proposal is based on the demonstrated tendency for physical attractiveness to been seen as affecting a person's opportunities. For example, Rohner and Rasmussen () showed that physically attractive individuals are perceived to possess a greater number of socially desirable traits. Furthermore, studies have illustrated that attractive individuals are viewed as having greater competence (Verhulst, Lodge, & Lavine, ) and higher levels of achievement and initiative (Chia, Allred, Grossnickle, & Lee, ).…”
mentioning
confidence: 99%
“…Furthermore, as stereotypecongruent information is recalled more readily than stereotype-incongruent information, such information may offset the influence of stereotype inconsistent information in decision making. Rohner and Rasmussen (2012) found that respondents recalled positive qualities in attractive targets and negative qualities in unattractive targets, regardless of actual information presented.…”
Section: Potential Mediators Of the Relationship Between Applicant Wementioning
confidence: 84%